2019
DOI: 10.1038/s41598-019-41661-9
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal development of pyramidal neurons across layers of the mouse medial prefrontal cortex

Abstract: Mammalian neocortex is a highly layered structure. Each layer is populated by distinct subtypes of principal cells that are born at different times during development. While the differences between principal cells across layers have been extensively studied, it is not known how the developmental profiles of neurons in different layers compare. Here, we provide a detailed morphological and functional characterisation of pyramidal neurons in mouse mPFC during the first postnatal month, corresponding to known cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 65 publications
14
75
0
Order By: Relevance
“…Rapid increase of the OTR expression in P14-21 corresponds with the peak time of synaptic formation and maturation in rodent brains 56,57 . Synaptic maturation patterns differ in cortical layers during early postnatal periods 58,59 . For example, tactile stimulus specific activity pattern emerges in the superficial layers of the barrel cortex that is subsequently followed by deep layer maturation in mice 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Rapid increase of the OTR expression in P14-21 corresponds with the peak time of synaptic formation and maturation in rodent brains 56,57 . Synaptic maturation patterns differ in cortical layers during early postnatal periods 58,59 . For example, tactile stimulus specific activity pattern emerges in the superficial layers of the barrel cortex that is subsequently followed by deep layer maturation in mice 59 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this period corresponds to an important stage in the initiation of neural circuit formation, which includes dendritic outgrowth and synaptic production in the mPFC. In fact, it has been reported that a developmental peak in prefrontal cortex volume occurs from the first to the second week after birth [36], and dendritic arborization and length in the mPFC rapidly increase during this period [37,38]. In addition, during the first postnatal week, mediodorsal thalamic projections precede neural circuit formation in the prefrontal cortex [39].…”
Section: Discussionmentioning
confidence: 99%
“…Brains were harvested and mCherry+, BFP+ and GFP puncta+ neurons were analyzed at P30 (Fig. 9C), when pyramidal cortical neurons are morphologically and synaptically mature (50). Adnp deficient dendrites had significantly more puncta compared to Scramble shRNA dendrites (Fig.…”
Section: Resultsmentioning
confidence: 99%